Gestión administrativa y su incidencia en la efectividad de las actividades académicas en la unidad educativa “el Empalme”, cantón el Empalme provincia del Guayas - Morales Aragundi, María Auxiliadora (2015)
The research process has as main objective, determining ADMINISTRATIVE MANAGEMENT AND ITS IMPACT ON THE EFFECTIVENESS OF ACADEMIC ACTIVITIES IN EDUCATIONAL UNIT "JUNCTION" El Empalme Canton Province of Guayas 2015. In terms of methodology of work, They applied the methods: deductive, inductive, analytic and synthetic, which served to process the empirical data as well as for the analysis of cases, to make comparisons and relationships, which allowed us to understand the causes that caused the problem in the academic and administrative development of the institution; They were also helpful in drawing conclusions, check and verify the assumptions and establish general criteria on the issue investigated. The technique used as an aid to data collection was the survey, which allowed us to know and have a general idea about the administrative and academic activities of the institution. After the investigation it was found that in the planning, organization, management, control and evaluation of the administration not involved teachers, students and parents holistically; besides, it was deduced that the administrative process, there is centralization of functions, dysfunctional in planning projects, mismanagement of resources, lack of socialization of the institutional evaluation processes, resistance to evaluation, lack of communication and institutional motivation. With regard to academic offerings there is close monitoring of the process of training the student is provided, as it refers in rigorous, academic aspect, based on the guidance in this context provides the Ministry Education underestimated. After the process of analysis, systematization and interpretation of the results obtained in the field work, it is determined that the assumptions made are approved.